Therapeutic outcomes and prognostic factors in unresectable gallbladder cancer treated with gemcitabine plus cisplatin - Min su You (BMC Cancer, 2019)
Abstract Background Gallbladder cancer (GBC) is likely to be diagnosed at progressive stages and shows a very poor prognosis. Combination therapy with gemcitabine and cisplatin (GEMCIS) has been widely used as first-line palliative chemotherapy for advanced GBC. This study was designed to investigate the efficacy of GEMCIS and identify prognostic factors in patients with unresectable GBC. Methods Patients with GBC who were treated with GEMCIS from January 2008 to June 2017 in a single tertiary hospital were included. All cases of GBC were diagnosed by pathologic findings and extent of the tumour was assessed by imaging tests. Combination chemotherapy consisted of cisplatin 25 mg/m2 and gemcitabine 1000 mg/m2 intravenously on days 1 and 8 every 3 weeks. To determine factors affecting prognosis, Kaplan–Meier survival analysis, log-rank test and the Cox proportional hazard regression linear model were used. All variables with P < 0.1 in univariable analysis were included in the multivariable model. Results A total of 173 patients received a median of 5.3 ± 4.4 cycles of chemotherapy over 3.8 ± 3.9 months. Most of the patients (94.8%) were stage IVB at the time of diagnosis and the most common site of metastasis was the liver (42.8%). Disease control rate was 59.5%: 2 (1.2%) patients with complete response, 26 (15.0%) patients with partial response and 75 (43.4%) patients with stable disease. Overall survival (OS) and progression-free survival were 8.1 (95% confidence interval [CI], 7.1–10.2) and 5.6 (95% CI 4.5–6.8) months, respectively. Multivariable regression model indicated that metastasis to liver (hazard ratio [HR] = 1.63, 95% CI 1.11–2.40; P = 0.013), neutrophil-to-lymphocyte ratio (NLR) ≥3 (HR 1.65, 95% CI 1.09–2.49; P = 0.017), CEA ≥ 5 ng/mL (HR 1.50, 95% CI 1.02–2.19; P = 0.038), and CA19–9 ≥ 500 U/mL (HR 1.59, 95% CI 1.01–2.50; P = 0.043) were significantly associated with OS. Conclusions GEMCIS demonstrated a high disease control rate in patients with unresectable GBC. Factors independently related to OS were metastasis to liver, NLR ≥ 3, CEA ≥ 5 ng/mL and CA19–9 ≥ 500 U/mL.